Descriptions of five new species of the family Lecithoceridae from Thailand (Lepidoptera: Gelechioidea) - K.-T. Park; H.-U. Kim (SHILAP, 2021)
Five new species of the family Lecithoceridae are described from Thailand: two new species of Torodorinae (Lepidozonates verberis Park, sp. n. and Torodora hispiduana Park, sp. n.) and three new species of Lecithocerinae (Lecithocera indanonensis Park, sp. n., Lecithocera petalialis Park, sp. n., and Opacoptera kerastiodes Park, sp. n.). In addition, Eccedoxa lysimopa (Meyrick, 1933) is reported for the first time from Thailand.